Contribution of capsaicin-sensitive sensory neurons to antithrombin-induced reduction of ischemia/reperfusion-induced liver injury in rats - Harada, Naoaki; Okajima, Kenji; Yuksel, Mehtap; Isobe, Hirotaka (Thrombosis and Haemostasis, 2005)
We previously reported that antithrombin (AT) reduced ischemia/ reperfusion (I/R)-induced liver injury in rats by increasing endothelial production of prostacyclin (PGI2). However, the mechanism(s) underlying this phenomenon remains to be fully elucidated. We also demonstrated that activation of capsaicinsensitive sensory neurons increased endothelial production of PGI2 by releasing calcitonin gene-related peptide (CGRP) in rats subjected to hepatic I/R. In the present study, we investigated whether AT increases endothelial production of PGI2 through activation of the sensory neurons in rats subjected to hepatic I/R. AT significantly enhanced the I/R-induced increases in hepatic tissue levels of CGRP in rats. Increases in hepatic tissue levels of 6-keto-PGF1α, a stable metabolite of PGI2 , the increase in hepatic-tissue blood flow, and attenuation of both hepatic local inflammatory responses and liver injury in rats administered AT were completely reversed by administration of capsazepine, an inhibitor of sensory neuron activation and CGRP(8–37), a CGRP antagonist.AT did not show any protective effect on liver injury in animals undergoing functional denervation by administration of a large amount of capsaicin.AT significantly increased CGRP release from cultured dorsal root ganglion neurons isolated from rats in the presence of capsaicin.Taken together,these observations strongly suggested that AT might increase hepatic tissue levels of PGI2 via enhancement of hepatic I/R-induced activation of capsaicin-sensitive sensory neurons,thereby reducing liver injury in rats. In this process, CGRP-induced activation of both endothelial nitric oxide synthase and cyclooxygenase-1 might be critically involved.
Keywords: Antithrombin; ischemia/reperfusion; capsaicin-sensitive sensory neurons; calcitonin gene-related peptide; prostacyclin